Micro- and nanoindentation techniques for mechanical characterisation of materials - Mukhopadhyay N.K.; Paufler P. (My University, 2025)
Indentation techniques have been extensively used for mechanical characterisation of materials. Development of instrumented indentation techniques at low and ultra low load levels has further improved their utility for understanding the mechanical responses of solids at micro and nano scales. The variation of hardness with the load/depth of indentation, known as indentation size effect, has led to difficulties in using hardness as a fundamental or characteristic mechanical property of materials. Detailed discussions are focused on the issue of indentation size effect in brittle and ductile solids. Various theoretical models accounting for the indentation mechanics are highlighted. The results obtained from these techniques with quasicrystals, bulk metallic glasses and nanomaterials are reviewed. The issues related to phase transformation during indentation tests are briefly discussed. The industrial use of the indentation technique has been pointed out. Some of the current issues and directions for future research in this field are mentioned. © 2006 Institute of Materials, Minerals and Mining and ASM International.